Saudi Arabia : Almarai and Vision 2030 - Osland, Asbjørn, (SAGE Business Cases., 2021)
Key focuses in the Kingdom of Saudi Arabia's (KSA) Vision 2030 were to diversify the economy beyond oil and to create jobs for Saudis. Although the creation of Almarai in 1977 preceded the promulgation of Vision 2030 in 2016, Almarai's dairy business and other food services are consistent with Vision 2030 in terms of diversification beyond oil and creating jobs for Saudis. Petroleum related products constitute more than 90% of the nation's exports. Almarai has the largest dairy farm in the world, which creates jobs in the food industry for Saudis. Almarai's business is vertically integrated from farms to production and distribution. To produce alfalfa for cattle feed, it bought land in Argentina in 2012, in Arizona in 2014, in California in 2015, and Romania in 2019 for its dairy herd of 170,000 cattle. The international land purchases allowed the KSA to phase out domestic alfalfa production. In 2016, the KSA launched a 3-year program to reduce KSA-based production of alfalfa and other commodities used as inputs for dairy and livestock production. It was imprudent to grow alfalfa in the KSA because this activity would seriously deplete the aquifers.The case involves three basic issues. First, importing alfalfa grown with scarce water in the parched areas of southern California and Arizona to the KSA is controversial. Should Americans living in the area have an ethical claim to this water, a scarce and vital resource? A second issue is the KSA's desire to import some food and grow inputs like alfalfa abroad on purchased or leased agricultural land. Was this a viable strategy? Finally, the third issue is domestic production to diversify the industrial base, provide jobs for Saudis, and provide domestically produced food. The KSA feared the impact of COVID-19 and other crises could disrupt supply chains. However, locally produced food would never satisfy its growing population. Did it make economic and political sense to support a venture such as Almarai?